FDI and FPI: strategic complements? - Barbara Pfeffer (Philipps-University Marburg, Faculty of Business Administration and Economics, 2008)
We show in a dynamic investment setting whether firms choose FDI or international portfolio investment (FPI) in the presence of stochastic productivity taking into account differences in flexibility of both investments. Isolated FPI and FDI investments are compared to combined FPI and FDI investments. FDI requires higher investment specific costs than FPI. Thus, it is not possible to adjust FDI to environmental changes every period. In contrast, FPI bears lower fixed costs and can be adjusted immediately to short-term changes in the environment. Additionally, as a result of the investors. control position FDI yields a higher return than FPI. Hence, there is a trade-off between flexibility and higher return for firms deciding between FDI and FPI. We explore whether as a consequence of higher investment specific fixed costs and lower flexibility in the case of FDI, small firms prefer FPI and larger firms invest in FDI. We show that a combined strategy dominates the isolated strategy always in times. Further, combined international investment comprises a higher incentive for firms to invest in r&d-investment and consequently firm productivity increase faster than with isolated international investment. Depending on the success-probability and the correlation between the various investment possibilities, even small firms (low productivity) invest in FDI.
Keywords: F21; F23; G11; 330; FDI; Portfolio Investment; Risk Diversification; endogeneous Productivity